2016
DOI: 10.1016/j.jdiacomp.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional and morphological alterations of the urinary bladder in type 2 diabetic FVBdb/db mice

Abstract: Aims Diabetic bladder dysfunction (DBD) has been extensively studied in animal models of type 1 diabetes. We aimed to examine the functional and morphological alterations of the urinary bladder in a type 2 diabetes model, FVBdb/db mice. Methods FVBdb/db mice and age-matched FVB/NJ control mice were tested at either 12, 24 or 52 weeks of age. Body weight, blood glucose and glycated hemoglobin (HbA1c) levels were measured. Bladder function was assessed by measurement of 24-hour urination behavior and conscious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Gharaee-Kermani et al (2013) suggested that obesity, DM, lower urinary tract fibrosis and urinary voiding dysfunction are inextricably and biologically linked [29]. Diabetes-associated alterations in collagen (tissue stiffness) have been described in human studies of vascular stiffness [30] and skeletal muscles [31], in various animals studies of the urethra [26,32], and in studies of the urinary bladder in rats [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Gharaee-Kermani et al (2013) suggested that obesity, DM, lower urinary tract fibrosis and urinary voiding dysfunction are inextricably and biologically linked [29]. Diabetes-associated alterations in collagen (tissue stiffness) have been described in human studies of vascular stiffness [30] and skeletal muscles [31], in various animals studies of the urethra [26,32], and in studies of the urinary bladder in rats [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…At least six reproducible micturition cycles were recorded and used to quantify multiple parameters. Specifically, intercontractile interval (ICI, time between micturition events), maximal voiding pressure (VP), bladder capacity (BC, defined as the saline infusion rate mu ltiplied by the intercontractile interval), void volume (VV), and non-voiding bladder contraction (NVC, intravesical pressure increases >5 mmHg during the filling phase, without the release of fluid from the urethra) and voiding efficiency (VE, voided volume/bladder capacity × 100) were determined (Vera and Nadelhaft, 2001 ; Füllhase et al, 2013 ; Lai et al, 2016 ; Wu et al, 2016 ). Estrous cycle phase in female mice was not recorded prior to conducting cystometry.…”
Section: Methodsmentioning
confidence: 99%
“…After an initial stabilization period of about 30 min, 6‐8 reproducible micturition cycles were recorded. Although the number of micturition cycles differed among animals, the means were calculated to analyze CMG parameters …”
Section: Methodsmentioning
confidence: 99%